A procedure to design toe protections for rockfill dams against extreme through-flows. (15th September 2019) - Morán, Rafael; Toledo, Miguel Á.; Larese, Antonia; Monteiro-Alves, Ricardo
Highlights: A new methodology for designing rockfill dam protections using rockfill toes is presented. A combination of numerical and experimental research was used during the research. Such methodology has been experimentally validated in laboratory conditions. The article shows the main result of a PhD Thesis (Technical University of Madrid). Abstract: This article presents a procedure for designing rockfill toe protections with a highly permeable downstream shoulder to avoid mass sliding in dams during extremely high through-flow episodes. This accidental through-flow may be caused by reasons such as overtopping or leakage flow due to the loss of sealing at the impervious element of the dam or its foundation. The proposed protection is located at the downstream toe of the dam, and it is composed of highly permeable material, typically compacted rockfill. This material can be different from the rockfill forming the downstream shoulder of the main dam. The work is a result of a combination of numerical and experimental research carried out to analyze the influence of the geometry of the toe protection for given material properties of both dam shoulder and protection, when they can be considered highly isotropic. As a result of these studies, a design methodology is obtained. A series of validation tests are presented to support the reliability of the method.